ДИЈАГНОСТИЧКА И ПРОГНОСТИЧКА ВРЕДНОСТ СЕЛЕНА И СЕЛЕНОПРОТЕИНА P КОД БОЛЕСНИКА СА КОМОРБИДНИМ ТОКОМ БЕЗАЛКОХОЛНЕ БОЛЕСТИ МАСНЕ ЈЕТРЕ И АРТЕРИЈАЛНЕ ХИПЕРТЕНЗИЈЕ - Tverezovska, Iryna (Medicinski časopis, 2022)
Objective. To evaluate the diagnostic and prognostic value of selenoprotein P and selenium in the progression of liver damage in patients with NAFLD. Methods. The study involved 120 patients: 50 with isolated NAFLD, 50 - with comorbid NAFLD and hypertension, established according to the world and local guidelines. Liver function parameters, selenium and Selenoprotein P levels were assessed, and predictors of steatohepatitis were identified. Pearson’s χ2, Mann-Whitney test, logistic regression were used. Results. The study found significant predominance of levels of Selenoprotein P (Sel P) and selenium in controls (71.0 [54.3; 76.1] ng/ml and 108.0 [96.9; 118.8] ng/ml respectively) compared with the NAFLD + hypertension (19.7 [8.0; 26.7] ng/ml and 43.5 (39.9; 49.1] ng/ml, p <0.001) and the NAFLD group (43.1 [41.3; 45.4] ng/ml and 67.2 [61.5; 77.4] ng/ml, respectively, p <0.001). Regression analysis determined association of Sel P and Sel levels with steatohepatitis: respectively, OR = 1,143 [95.0% CI 1,068–1,224] (p <0.001) and OR = 1,054 [95.0% CI 1,012–1,098] (p = 0.011). Other predictors of steatohepatitis were aspartateaminotransferase (OR = 1,421 [95.0% CI 1,198–1,687], p <0.001) and systolic blood pressure (OR = 1,089 [95.0% CI 1,017–1,116], p = 0.014). Conclusions. Levels of selenium and selenoprotein P are associated with greater liver damage in patients with NAFLD, and the concomitant increase in systemic blood pressure is an additional factor that adversely affects the course of NAFLD, increasing the intensity of liver damage in such patients.